The effect of water vapor diffusion resistance factor of insulation materials for outer walls on condensation - Bademli?Oğlu, Ali Hüsnü; Kaynakli, Ömer; Yamankaradeniz, Nurettin (Turk Isı Bilimi ve Teknigi Dernegi Maltepe, ANKARA 06570, 2018)
Condensation, which is the result of water vapor diffusion, affects the heat transfer in the building material negatively. The condensation which is seen mostly in winter seasons at building materials, occurs when the surface temperature of the building material in contact with air falls below the raw temperature of the air. In this case, condensed water may cause mildew, fungal growth, odors, and deterioration of dye and building materials or adversely affected thermal insulation on the walls. Materials used for thermal insulation in buildings constitute resistance against water vapor diffusion. Water vapor diffusion resistance factor (VDRF) of materials can vary over a wide range. In this study, considering VDRF range that is commonly encountered in insulation applications, the effect of VDRF of insulation materials on condensation within constructions, and on the minimum thickness of insulation required to prevent this condensation accordingly were examined. Externally insulated wall was taken as sample wall model, heat and mass transfer calculations from wall unit area and insulation thickness minimization were performed for different indoor-outdoor temperatures and relative humidity values. As a result of the analysis conducted, in constant indoor-outdoor conditions in general, as VDRF increases, the risk of condensation inside the wall first decreases and then increases. Minimum insulation thickness that is required to be applied to prevent condensation also shows a similar trend depending on the VDRF. For constant VDRF, it was come to the conclusion that as the difference between indoor-outdoor temperatures and relative humidity increases, the risk of condensation and consequently required insulation thickness increases. ©2018 TIBTD Printed in Turkey.
Keywords: Condensation; Insulation; Thermal conductivity; Water vapor diffusion resistance factor